Conflict Analysis in Denis Villeneuve’s film Prisoners - Syamsul Bahri; Putri Naira; Fitra Aulia Simatupang; Farid Rizaldi (STIKes Ibnu Sina Ajibarang, 2025)
The film Prisoners (2013), directed by Denis Villeneuve, presents a complex portrayal of emotional intensity, moral ambiguity, and psychological struggle in the aftermath of a child kidnapping. Conflict becomes the central element that shapes the characters, drives the storyline, and raises important questions about justice, resilience, and ethical boundaries. This study aims to explore the internal and external conflicts found in Prisoners, and how these tensions reflect challenges often encountered in real life. Using a descriptive qualitative method and based on William Kenney’s theory of conflict, the research closely analyzes key scenes and character interactions to identify patterns of tension and confrontation. The results show that Prisoners features 15 conflict events: internal conflict (26.67%), man vs. man (33.33%),man vs. society (26.67%), and man vs. nature (13.33%), with with man vs. man emerging as the most dominant, emphasizing the focus on intense personal struggles and confrontations between characters. The findings suggest that Prisoners (2013) uses conflict not just as a narrative device, but also as a way to invite the audience to reflect on moral choices, human limits, and the emotional cost of seeking justice in moments of crisis.